The role of E2F2 in cancer progression and its value as a therapeutic target - Gao, Yang; Qiao, Xinjie; Liu, Zhenhui; Zhang, Wenzhou (Frontiers in Immunology, 2024)
The E2F family of transcription factors plays a crucial role in the regulation of cell cycle progression and cell proliferation. Accumulative evidence indicates that aberrant expression or activation of E2F2 is a common phenomenon in malignances.E2F2 has emerged as a key player in the development and progression of various types of tumors. A wealth of research has substantiated that E2F2 could contribute to the enhancement of tumor cell proliferation, angiogenesis, and invasiveness.Moreover, E2F2 exerts its influence on a myriad of cellular processes by engaging with a spectrum of auxiliary factors and downstream targets, including apoptosis and DNA repair. The dysregulation of E2F2 in the context of carcinogenesis may be attributable to a multitude of mechanisms, which encompass modifications in upstream regulatory elements or epigenetic alterations. This review explores the function of E2F2 in cancer progression and both established and emerging therapeutic strategies aiming at targeting this oncogenic pathway, while also providing a strong basis for further research on the biological function and clinical applications of E2F2.